Aberrantly glycosylated PSMA in urine as a potential marker for prostate cancer - Khan, Misba; Islam, Md. Khirul; Taimen, Pekka; Boström, Peter J.; Lamminmäki, Urpo; Leivo, Janne (Elsevier BV, 2026)
Early detection of prostate cancer (PCa) requires the development of reliable non-invasive biomarkers. In this study, we describe a simple, non-invasive assay to detect a prostate-specific membrane antigen (PSMA) glycoisoform directly from unprocessed urine. PSMA was analyzed in urine samples from PCa patients (n = 40) and benign controls (n = 37) using lectin MGL-coated europium-doped nanoparticles. MGL showed enhanced binding to PCa-derived PSMA, indicating aberrant glycosylation. Evaluation of individual samples demonstrated that the PSMA-MGL glycovariant assay significantly discriminated PCa from benign conditions (p = 0.01 pilot, p = 0.02 validation). Moreover, this assay exhibited a three-fold improvement in sensitivity over conventional antibody-based PSMA detection. ROC analysis showed an AUC of 0.648 for PSMA-MGL, which increased to 0.734 when combined with free-PSA and urinary creatinine, highlighting the enhanced diagnostic potential of this multimarker, non-invasive approach.